Modulation of Plant Defense System in Response to Microbial Interactions - Nishad, Resna; Ahmed, Talaat; Rahman, Vattakandy Jasin; Kareem, Abdul (Frontiers in Microbiology, 2020)
At different stages throughout their life cycle, plants often encounter several pathogenic microbes that challenge plant growth and development. The sophisticated plant innate immune system prevents the growth of harmful microbes via two interconnected defense strategies based on pathogen perception. These strategies involve microbe-associated molecular pattern-triggered immunity and microbial effector-triggered immunity. Both these immune responses induce several defense mechanisms for restricting pathogen attack to protect against pathogens and terminate their growth. Plants often develop immune memory after an exposure to pathogens, leading to systemic acquired resistance. Unlike that with harmful microbes, plants make friendly interactions with beneficial microbes for boosting their plant immune system. A spike in recent publications has further improved our understanding of the immune responses in plants as triggered by interactions with microbes. The present study reviews our current understanding of how plant–microbe interactions can activate the sophisticated plant immune system at the molecular level. We further discuss, how plant-microbe interaction boost the immune system of plants by demonstrating the examples of Mycorrhizal and Rhizobial association and how these plant-microbe interactions can be exploited to engineer disease resistance and crop improvement.